Elaboração de programa de enriquecimento ambiental para catetos (Dicotyles tajacu) e queixadas (Tayassu pecari) do Criadouro Comercial Fazenda Trijunção - Salmazo, Julia Rodrigues (Universidade Federal de São Carlos, 2025)
Animal welfare is a growing concern among professionals and institutions that keep wild animals. Tools such as environmental enrichment are important in this search for welfare, in addition to assisting in other aspects that directly or indirectly affect the conservation of species, such as reproduction. Captive breeding is an important strategy to promote conservation and prevent the populational decline of a species. Among the native species with the greatest productive potential in captivity are the collared peccary (Dicotyles tajacu) and the white-lipped peccary (Tayassu pecari). The Fazenda Trijunção Commercial Breeding Center has a large number of collared and white-lipped peccaries in its collection, and one of its priorities is their welfare. This study aimed to apply and evaluate environmental enrichment activities to support the development of an environmental enrichment program for collared and white-lipped peccaries at the Fazenda Trijunção Commercial Breeding Center. Six activities of three stimulus categories (physical, feeding and sensorial) were applied, which were analyzed by recording, evaluating and comparing the behaviors displayed before and during the application. For the behavioral analysis, observation was performed by using the scan method with instantaneous recording at three-minute intervals, for four hours in the pre-enrichment period and four hours in the enrichment period, for both species and for each sex. The relative frequency of display of each behavioral category was calculated, focusing on the “EA” behavior, which reflects the interaction of the animals with the enrichments. The behavioral data were statistically evaluated with generalized linear models (GLM). Although no statistical differences were identified in the interactions with each enrichment (p > 0.05), an increase in the general activity of the individuals and a reduction in inactivity were observed. A tendency of the animals to interact more with feeding enrichments was also identified. Based on these informations, a solid environmental enrichment program was structured, with planning sheets, schedule and evaluation of the activities. The program developed represents a step forward in promoting the welfare of this institution's animals and could serve as a replicable model for others.
Development of an environmental enrichment program for collared peccaries (Dicotyles tajacu) and white-lipped peccaries (Tayassu pecari) at the Fazenda Trijunção Commercial Breeding Center
Keywords: Bem-estar; Comportamento animal; Tayassuidae; Criação em cativeiro; Welfare; Animal behavior; Captive breeding; CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS